Implementation of Consumer Protection from a Human Rights Perspective in Indonesia - Agustin Widjiastuti; Nafis Dwi Kartiko; Ina Rosmaya (UIN Sunan Kalijaga Yogyakarta, 2025)
The development and advancement of information technology has led to new legal activities being carried out virtually, such as electronic transactions. While online electronic transactions offer advantages, there are also risks that can harm consumers. With the enactment of Consumer Protection Law No. 8 of 1999, Financial Sector Development and Strengthening Law No. 4 of 2023, and the Electronic Information and Transactions Law, as well as other laws, does this provide protection for consumer rights, which are human rights, when consumers suffer losses? Legal measures that hinder consumers from obtaining protection when conducting electronic transactions create an imbalance in transactions from a human rights perspective. The research method used in this study is a normative juridical research method, which is an effort to find solutions to problems by examining and reviewing positive legal norms using the concept of Law in book, namely by conducting a literature study. The results of the study show that government policies, which should provide rules to guarantee the public interest, preventative measures, and legal protection for consumers through existing regulations and law enforcement, as well as improve welfare and social justice for all citizens, can be reflected/implemented through policies carried out in accordance with the principles outlined in the general principles of good governance. However, there is still a need for improvement in implementing existing policy principles by emphasizing the importance of optimal strict regulation and law enforcement related to government actions, as well as maintaining public trust and community compliance in accordance with a human rights perspective.